Формування сучасного правового термінологічного апарату в івриті: способи та вплив інших правових систем - Яковлева, О.; Цвєткова, Ю. (Київський національний університет імені Тараса Шевченка, 2024)
Досліджено особливості формування правових термінів у процесі відродження івриту та перетворення його на державну мову сучасного Ізраїлю. Правова система Ізраїлю створювалася протягом ХХ ст., а правовий термінологічний апарат івриту ґрунтувався на стародавніх джерелах, створення або пристосування класичних івритських слів для визначення сучасних правових термінів стало науковим викликом. У статті доводиться, що під час формування правової термінології на івриті не створювалися нові лексеми, а застосовувалися слова зі стародавніх текстів із певним переосмисленням їхнього змісту. Хоча за основу багатьох базових термінів були взяті поняття саме з англійської правової системи, разом із тим, під час створення термінів акцент робився не тільки на формальній назві англійських правових інститутів та її етимології, але процес відбувався значно глибше, з урахуванням змісту та механізмів реального правозастосування.

The article is dedicated to the peculiarities of the legal terminology formation, which took place in the process of the restoration of the Hebrew language and its becoming the official state language of the modern Israel. The legal system of Israel has been created during XX century, after near two-thousand-year period of its existence without own state, being limited to the small community's common and religious law in different languages only. Thus, creation of the own state has demanded not only to adapt the legal institutes, but to develop new actual terminology in the new official state language. But the terminology complex of the Hebrew was based on the ancient language sources, so creation or adapting of the classic Hebrew words for the definition of the modern legal terms became a great scientific challenge. In the article we conclude, that new lexemes were not created in the process of the Israel legal terminology formation, but the old texts words were chosen, usually with some rethinking and reinterpretation of its meanings. This approach provides the possibility to avoid direct borrowing of the terms, which is a typical process in the reception of law in other states. Despite the fact that, in addition to the English Common Law, the formation of Israel's legal system was influenced by the Ottoman and Romano-Germanic law, concepts from the English legal system were taken as the basis for the selection of many basic terms. The terms creation was not limited to formal denomination only. Often the process becomes more substantive, noticing the etymology, the content of the legal institute and the mechanisms of the practical law-enforcements. After this deep scientific work of the linguists and lawyers Hebrew terminology of the Israel legal system fully expresses the content and the scope of the concepts of the relevant legal institutes.
The forming of the modern legal terminology in Hebrew: methods and other legal system influence
Keywords: термінотворення в івриті; відродження івриту; правова термінологія; правова система Ізраїлю; terminology creation in Hebrew; restoration of Hebrew; legal terminology; legal system of Israel